Upaya Penggunaan Buku Pop Up Untuk Meningkatkan Kemampuan Literasi Membaca Siswa - Niswatul Hasanah; Siti Zulfiana; Zuri Anggraini (BALE LITERASI, 2025)
Introduction to reading literacy requires engaging learning media to increase children's interest. However, the use of engaging learning media, particularly in Al-Hamzar Islamic Kindergarten, is still not optimal. The purpose of this study was to improve reading literacy skills by using pop-up books in Al-Hamzar Islamic Kindergarten with 17 children in class B, consisting of 10 girls and 7 boys. This study is a classroom action research (CAR) consisting of two cycles. Each cycle consists of planning, implementation, observation, and reflection, and each cycle is carried out with 3 meetings. The data collection techniques used are observation and documentation. The results of the study in the pre-cycle, cycle I, and cycle II are as follows: in the pre-cycle, the number of children who achieved the criteria for developing according to expectations (BSH) was 4 children or 24%. In cycle I, the number of children who achieved the criteria for developing according to expectations (BSH) and developing very well (BSB) was 9 children or 53%. In cycle II, 14 children, or 82.1%, met the criteria for developing as expected (BSH) and developing very well (BSB). Therefore, this study can be considered successful, meeting the minimum indicator of 75%.